Histoarchitecture of Harderian Gland in Turkeys at Pre-pubertal Age - Jayachitra, S.; Sivagnanam, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during August, 2021 to June, 2022 at the Department of Veterinary Anatomy, Veterinary College and Research Institute, Namakkal, Tamilnadu, India to elucidate the histological features to provide reference to physiology, immunology and pathology. The harderian gland samples were collected from Broad Breasted Bronze varieties of turkeys immediately after slaughter. Those were collected from turkeys at 5 months of age before sexual maturity, earlier in the year 2021. The Harderian gland of turkey was compound tubulo-acinar type covered by connective tissue capsule. The inter-lobar septa from the capsule divided the glandular parenchyma into many variously sized and shaped lobes filled with secretory units. The capsule and septa showed collagen, elastic and reticular fibers with numerous fibrocytes and fibroblasts. Each lobe had a secretory component and a lymphoid component. The secretory part was lined by pyramidal cells in acini and columnar cells in tubular units and both had spherical nucleus at base. The lymphoid component was constituted by various populations of lymphoid cells such as lymphoblasts, small, medium and large lymphocytes. It also showed numerous plasma cells. Each lobe had a central duct surrounded by several acinar and tubular secretory units. Each secretory unit was lined by closely attached pyramidal cells in acini and columnar cells in tubular units. Myoepithelial cells were noticed at the base of secretory units. The central duct of each lobe was wide and irregular in shape with many crypts and was drained into a large main duct which extended from the posterior to anterior end of the gland.